If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (19b + -3) + -6(3b + 2) = -7 Reorder the terms: (-3 + 19b) + -6(3b + 2) = -7 Remove parenthesis around (-3 + 19b) -3 + 19b + -6(3b + 2) = -7 Reorder the terms: -3 + 19b + -6(2 + 3b) = -7 -3 + 19b + (2 * -6 + 3b * -6) = -7 -3 + 19b + (-12 + -18b) = -7 Reorder the terms: -3 + -12 + 19b + -18b = -7 Combine like terms: -3 + -12 = -15 -15 + 19b + -18b = -7 Combine like terms: 19b + -18b = 1b -15 + 1b = -7 Solving -15 + 1b = -7 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 1b = -7 + 15 Combine like terms: -15 + 15 = 0 0 + 1b = -7 + 15 1b = -7 + 15 Combine like terms: -7 + 15 = 8 1b = 8 Divide each side by '1'. b = 8 Simplifying b = 8
| 25m=13 | | -8(2t+5)=-120 | | z+113=978 | | 2x+9x=77 | | 2(f-4)=-18 | | 595=-17s | | n=n*n-90 | | -10(s+4)=44 | | 875=25n | | 56=s-907 | | 852=b-8 | | 8(4s+1)=296 | | v-690=946 | | 2(8-x)=8 | | 2(2l+9)=26 | | z+30=987 | | 84=z+8 | | 10-48x+36x^2=0 | | q-9*5=45 | | q+272=-132 | | 6x(3-x)=x-y | | Y=400-30X-X^2 | | 20C=15 | | g-739=-102 | | -0.5x^2+x+20.62=0 | | 6=0.08*x | | y+68=475 | | 8x^2-24x-144-y^2=0 | | y=400-30x-2x | | 6x+3x-y=4y | | 88=q+33 | | 980=-2b |